Incidental pineal gland cyst in girls with early onset of puberty - Gianpaolo De Filippo; Rossella Gaudino; Valeria Calcaterra; Alberto Villani; Elena Bozzola; Mauro Bozzola (BMC, 2022)
Abstract Background The causes of an early onset of puberty are still not clearly defined and may vary from subject to subject. In girls, even if 90% of early puberty is idiopathic, magnetic resonance imaging (MRI) of the brain is performed to exclude secondary causes of precocious puberty, in particular pathological lesions as hypothalamic tumours (hamartoma). In some cases, other intracranial lesions are considered as incidental findings. Aim of the study is evaluating the prevalence of abnormal intracranial lesions detected by brain magnetic resonance imaging MRI with particular focus on the prevalence of pineal gland cysts in the diagnostic work-up of girls with central precocious puberty (CPP) as onset before 8 years and central early puberty (CEP) as onset before 10 years. Material and methods MRI data of girls referred from January 2010 to December 2015 to the Pediatric Endocrinology Unit of University of Pavia for early onset of breast development were collected. Results We collected 123 MRI data of girls referred to the Pediatric Endocrinology Unit of University of Pavia for early onset of breast development in the study period. Out of them, 25 (20.3%) had cerebral abnormalities and 15 (12.2%) had pineal gland cysts. No significant differences were noted in auxological, ultrasound and hormonal parameters at diagnosis among girls with or without pineal cysts. Patients have been observed for at least three years after the discontinuation of therapy. None of our patients had an unfavorable evolution. Conclusions Although pineal cysts seem to be not involved in the onset of puberty, the relevance of the finding remains controversial. Our study wants to provide further insight into the incidence of pineal cysts in pubertal advances. Of note, pineal cysts are often asymptomatic and do not evolve over time.